Can we prevent ovarian cancer? - Aus, Ali Tariq (Ceska gynekologie, 2020)
INTRODUCTION: An ovarian cancer prevention program must encourage the application of factors associated with decreased risk that include both surgical and non-surgical approaches. Non-surgical preventive approaches include oral contraceptives, parity, multiparity and breastfeeding. In addition, approaches that decrease inflammation and oxidative stress such as regular exercise and a healthy diet are also important. Surgical approaches include tubal ligation, hysterectomy and prophylactic bilateral salpingo-oophorectomy. OBJECTIVE: To highlight protective approaches for the prevention of ovarian cancer in order to increase awareness among women of the general population and too find out whether or not these approaches are enough to prevent the disease. DESIGN: Review article. SETTING: Department of Chemical Pathology, NHLS, Tygerberg Hospital and Faculty of Medicine and Health Sciences, Stellenbosch University, Cape Town, South Africa. METHODS: Literary sources related to the topic were used. Articles were selected primarily based on PubMed and Google searches. CONCLUSION: Ovarian cancer cannot be prevented completely, however the application of preventive approaches may decrease the risk significantly. Although, multiparity followed by long periods of breastfeeding may not seem feasible for most today women, it is the most pronounced preventive approach for women in the general population. Tubal ligation, hysterectomy also reduce the risk significantly. Opportunistic salpingectomy may provide better prevention for women at average risk, while women at high risk (BRCA mutation and family with history of ovarian cancer) are advised to undergo risk-reducing salpingo-oophorectomy. Highlighting these approaches may increase women's awareness towards decreasing risk and decrease the incidence of ovarian cancer and potentially increase the five-year survival rate.
Keywords: epiteliální ovariální karcinom; breastfeeding; těhotenství; lidé; salpingektomie; nádory vaječníků; ovarektomie; contraceptives; prophylactic surgeries; profylaktické chirurgické výkony; Salpingo-oophorectomy; salpingo-ooforektomie; ženské pohlaví; Humans; Ovariectomy; physical activity; Pregnancy; Aspirin; parity; ovarian cancer; Carcinoma, Ovarian Epithelial; Female; Ovarian Neoplasms; Prophylactic Surgical Procedures; Salpingectomy